Undifferentiated Pleomorphic Sarcoma of Pancreas: A Case Report and Review of the Literature for the Last Updates - Sanei, Behnam (Case Rep Med, 2018)
The most prevalent type of soft tissue sarcoma is undifferentiated pleomorphic sarcoma (UPS) or previously known as malignant fibrous histiocytoma. It accounts over 20% of all soft tissue sarcomas and occurs most frequently in the extremities, trunk, and retroperitoneum. However, it has been rarely observed in the digestive system. Pancreas sarcoma represents less than 1% of all pancreatic tumors, and primary UPS of the pancreas is even rarer. It exhibits high recurrence and poor prognosis. In this case, a 72-year-old woman with a UPS tumor which was located in the pancreas head and neck without adhesion to the retroperitoneum will be discussed.